Menakar Eksistensi dan Perlindungan Hukum Terhadap Sengketa Hak Atas Tanah Masyarakat Hukum Adat Berdasarkan Hukum Positif Indonesia: (Studi Kasus Perkebunan Sawit di Kalimantan Selatan) - Inas Zulfa Sulasno; Farina Firda Eprilia (Jurnal Hukum Lex Generalis, 2022)
The polemic of customary land rights raises further questions regarding the existence and legal protection of indigenous peoples involving South Kalimantan oil palm plantation entrepreneurs, especially legal regulations that are still sectoral in nature and differing views on land, resulting in prolonged conflicts. The results of the research show that there are 3 factors that make the existence of ulayat rights recognized, namely The community, territory and inter-both factors that indigenous peoples have the rights. Meanwhile, legal protection can be in the form of formulating policies that present the government, indigenous peoples, and entrepreneurs.